EVALUASI PENYELENGGARAAN PROGRAM SARJANA PENDAMPING PENGGERAK PEMBANGUNAN OLAHRAGA - Endi Rustandi, - (2022)
The deployment of Sarjana Pendamping Penggerak Pembangunan Olahraga (SP3Or) is expected to be able to mobilize and encourage the community to adopt an active lifestyle. This study aims to determine and explain the effectiveness of the implementation of the SP3Or program which is principally oriented to program improvement and refinement. The author uses an evaluation research method with a Mixed methods approach. The CIPP (Context, Input, Process, Product) evaluation model was chosen for this evaluation because this model emphasizes completeness in evaluation within the larger framework. Data collection techniques using documentation, interviews and questionnaires. Based on the data analysis, the results of the study indicate that the Context evaluation is very appropriate based on the legal basis, objectives and analysis of community needs. Input evaluation shows that it is very appropriate based on human resource support, financial support, infrastructure, and program strategy. Process evaluation shows that it is very appropriate based on the implementation of the planned program. Product evaluation shows that it is very appropriate based on the results of monitoring and evaluation of program implementation. Until the period of 2019 in 108 sub-districts, the participation rate of the people of West Java in exercising reached an average of 51.6%. This shows that in general, the implementation of the SP3Or program is in accordance with the objectives, although in its implementation there are still many things that need to be improved. Keywords: Sports Participation, SP3Or, Evaluation, CIPP